Barukh Kurzweil and Modern Hebrew Literature - Diamond, James S. (Brown Judaic Studies, 2020)
This book is a study of one of the foremost critics of Hebrew literature, Barukh Kurzweil. Kurzweil provides a window into the growth of, and theoretical reflection on, Hebrew literature as both a national literature and one in conversation with European literature as well.